The functional abilities and their differences between the volleyball teams from the republic of macedonia and the republic of kosovo in pre-competetion period - Ibrahimi, N.; Ibrahimi, A.; Stankovska, Z.; Bratovcic, V.; Kostovski, Z. (Sport Scientific and Practical Aspects - International Scientific Journal of Kinesiology, 2020)
The study was conducted on a stratified sample of two subsamp!es of subjects to determine the level and differences in heart rate, blood lactate, anaerobic threshold, V02max. in volleyball players in the precompetition period. The sample of respondents was taken from the population of volleyball players, a total of 43, members of the representative teams of the volleyball lea gue of the Republic of Macedonia and the Republic of Kosovo. The study used a total of 6 variables to assess the functional abilities of female volleyball players. Using multivariate analysis of variance (MANOVA}, statistically significant differences between groups were found at the level of p = 0.00. Testing differences between arithmetic means for each variable with univariate analysis of variance (ANOVA}, where no statistically significant differences were found between the two teams.